Purification and characterization of an immunoglobulin A1 protease from Bacteroides melaninogenicus. - Mortensen, S B (1984)
Attention has recently been focused on bacterial proteases with the capacity to cleave immunoglobulin A (IgA proteases) as possible pathogenic factors in bacterial meningitis, gonorrhoea, and destructive periodontal disease. Here, we describe a method for the rapid purification of a specific IgA1 protease from Bacteroides melaninogenicus. The IgA1 protease was purified 6,172-fold with a yield of 9% by ammonium sulfate precipitation, DEAE-ion exchange chromatography, and separation on a preparative TSK-G 3000SWG high-pressure gel permeation chromatography column. The enzyme was specific for human IgA1 and cleaved a prolyl-seryl peptide bond in the hinge region of the alpha 1 chain between residues 223 and 224. The molecular weight of the enzyme was 62,000, the isoelectric point was 5.0, and the Km was 3.4 X 10(-6). The enzyme was active over a broad pH range and had maximal activity at pH 5.0. B. melaninogenicus IgA1 protease was classified as a thiol protease on the basis of its inhibition by traditional protease inhibitors and the fact that it was active only under reducing conditions.